Pembentukan Akrilamida Dalam Makanan Dan Analisisnya - Harahap, Yahdiana (UI Scholars Hub, 2006)
Acrylamide is a chemical substance which derived from acrylonitrile, is the material used in polyacrylamide production. Recent research has found acrylamide is contained in some food, especially food is rich in carbohydrate and treated in high temperature (more than 120Â°C). Due to its nature, acrylamide is classified as a hazardous material to be contained in humanÂ’s food. The International Agency for Research on Cancer (IARC) has classified acrylamide into group 2A (probably carcinogenic for humans). Many methods that used to analyse the acrylamide in some foods with sophisticated equipment, and in department of pharmacy FMIPA-UI there were also develop the method with simple extraction and conventional HPLC